Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Development of Novel Host-Associated Low-Temperature Probiotics (HALP) Tailored to Aquaculture Applications - Su-Jeong Lee; Young-Sun Lee; Yu-Ri Kim; Mi-Hyeon Jeon; Da-In Noh; Seong-Mok Jeong; Kang-Woong Kim; Eun-Woo Lee; Won Je Jang (Probiotics and Antimicrobial Proteins, 2026)

Ferroptosis modulation by Toxoplasma gondii suppresses sodium iodate–driven age-related macular degeneration - Xin-Cheng Wang; Guan-Hao Hong; Yu-Sun Yun; In-Wook Choi; Jaemin Yuk; Guang-Ho Cha (Genes & Genomics, 2026)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Spatiotemporal distributions of total and methylmercury in bivalves from coastal zones of South Korea - Haein Yu; Geonwoo Park; Chul-In Sun; Yong Hwa Oh; Yong-Woo Lee (Marine Pollution Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Grifola frondosa extract as a fetal bovine serum supplement for the culture of bovine muscle satellite cells under low serum conditions - In-sun Yu; Sang Yoon Choi; Jungseok Choi; Mina K. Kim; Min Young Um; Jae Hwan Ahn; Min Jung Kim (Food Research International, 2024)

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Differences in macrophage polarization in the adipose tissue of obese mice under various levels of exercise intensity - Kyung-Wan Baek; Da-In Lee; Shin Ae Kang; Hak Sun Yu (Journal of Physiology and Biochemistry, 2020)

The medicinal mushroom Auricularia auricula - judae (Bull.) extract has antioxidant activity and promotes procollagen biosynthesis in HaCaT cells - Young-Ji Choi; In-Sun Park; Mi-Hee Kim; Bora Kwon; Young-Moo Choo; Seung-Il Jeong; Kang-Yeol Yu; Chung Hyeon Choe; Jiyoung Kim (Natural Product Research, 2019)

Reversine induces caspase-dependent apoptosis of human osteosarcoma cells through extrinsic and intrinsic apoptotic signaling pathways - Jae-Sung Kim; In-A Cho; Kyeong-Rok Kang; HyangI Lim; Tae-Hyeon Kim; Sun-Kyoung Yu; Heung-Joong Kim; Seul Ah Lee; Sung Min Moon; Hong Sung Chun; Chun Sung Kim; Do Kyung Kim (Genes & Genomics, 2019)

Effects of backcrossing on quality of strawberry fruit - Sun Yi Lee; Seung Yu Kim; Dae Young Kim; Ho Jeong Jeong; In Seok Um; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2018)

Identification and characterization of class I chitinase in Panax ginseng C. A. Meyer - Rama Krishna Pulla; Ok Ran Lee; Jun-Gyo In; Shohana Parvin; Yu-Jin Kim; Ju-Sun Shim; Hua Sun; Yeon-Ju Kim; Kalaiselvi Senthil; Deok-Chun Yang (Molecular Biology Reports, 2011)

Isolation and characterization of a Glutamate decarboxylase (GAD) gene and their differential expression in response to abiotic stresses from Panax ginseng C. A. Meyer - Jung-Hye Lee; Yu-Jin Kim; Dae-Young Jeong; Gayathri Sathiyaraj; Rama Krishna Pulla; Ju-Sun Shim; Jun-Gyo In; Deok-Chun Yang (Molecular Biology Reports, 2010)

Isolation of the groESL cluster from Vibrio anguillarum and PCR detection targeting groEL gene - Dong-Gyun Kim; Yu-Ri Kim; Eun-Young Kim; Hyun Min Cho; Sun-Hee Ahn; In-Soo Kong (Fisheries Science, 2010)

Isolation of S-adenosyl-L-methionine synthetase gene from Panax ginseng C.A. meyer and analysis of its response to abiotic stresses - Rama Krishna Pulla; Yu-Jin Kim; Shohana Parvin; Ju-Sun Shim; Jung-Hye Lee; Yeon-Ju Kim; Jun-Gyo In; Kalai Selvi Senthil; Deok-Chun Yang (Physiology and Molecular Biology of Plants, 2009)

Isolation and Characterization of a Glutaredoxin Gene from Panax ginseng C. A. Meyer - Yu-Jin Kim; Ju-Sun Shim; Pulla Rama Krishna; Se-Young Kim; Jun-Gyo In; Myung-Kyum Kim; Deok-Chun Yang (Plant Molecular Biology Reporter, 2008)

Enhanced brain targeting efficiency of intranasally administered plasmid DNA: an alternative route for brain gene therapy - In-Kwon Han; Mi Young Kim; Hyang-Min Byun; Tae Sun Hwang; Jung Mogg Kim; Kwang Woo Hwang; Tae Gwan Park; Woon-Won Jung; Taehoon Chun; Gil-Jae Jeong; Yu-Kyoung Oh (Journal of Molecular Medicine, 2006)

Random sequence analysis of genomic DNA of a hyperthermophile: Aquifex pyrophilus - In-Geol Choi; Sang Suk Kim; Jae-Ryeon Ryu; Ye Sun Han; Won-Gi Bang; Sung-Hou Kim; Yeon Gyu Yu (Extremophiles, 1997)